Radar observations in the vicinity of pre-noon auroral arcs - Nilsson, Hans; Kozlovsky, A.; Sergienko, T.; Kotikov, A. (CCSD, 2005)
International audience A combination of EISCAT incoherent scatter radar measurements, optical and magnetometer data is used to study the plasma in and around pre-noon structured precipitation and auroral arcs. Particular attention is paid to regions of comparatively low E-region density observed adjacent to arcs or structured precipitation in the EISCAT Svalbard radar field-aligned measurements. Comparison between luminosity and incoherent scatter electron density measurements shows that the low-density regions occur primarily due to the absence of diffuse precipitation rather than to a cavity formation process. Two cases of arcs and low density/luminosity regions are identified. The first is related to a strong Pc5 pulsation event, and the absence of diffuse precipitation is due to a large-scale modulation of the diffuse precipitation. In the second case the equatormost arc is on a shielding boundary and the low-density region coincides with a strong flow region just poleward of this arc. Regions of high electric field and low luminosity and conductance are observed prior to intensification of the structured precipitation in both cases. The ionospheric current is enhanced in the low conductance region, indicating that the strong electric fields do not result solely from ionospheric polarization electric fields, and thus are mainly driven by magnetospheric processes. The average energy of the precipitating electrons in the arcs and structured precipitation is, according to EISCAT measurements, 500eV and the energy spectra are similar for the pulsation and shielding cases. The average energy is thus significantly less than in the diffuse precipitation region which shows central CPS-like energy spectra. We suggest that the low ionospheric conductance of 0.7S in the low density regions is favorable for the arc formation process. This is in quantitative agreement with recent simulations of the ionospheric feedback instability. Keywords. Magnetospheric physics (Auroral phenomena; Magnetosphere-ionosphere ...